Design and Analysis of a Compact Metasurface Based Filter for Broadband Performance - Chauhan S.; Stephen S.; Carvalho F.; Kotrashetti A.; Ghosh S.; Bhattacharyya S. (My University, 2025)
In this paper, a planar metasurface based broadband low pass filter has been proposed for up to X-band. The unit cell of the proposed metasurface consists of a lattice made of Omega shaped geometric patterns etched on an FR4 substrate. The geometrical dimensions of the Omega structure have been varied to study their impact on the reflection and transmission characteristics of the filter. The structure provides insertion losses of less than 3 dB up to 12.5 GHz for a linear phase shift and constant minimum group delay throughout the passband. The proposed metasurface-based filter can be useful for weather forecasting, earth exploration services, airport surface detection equipment (ASDE) systems, etc. © 2022 IEEE.